219 Incidence Testing of Hunter Syndrome in A Population at Risk - First Results of A Binational Screening Programme. (October 2012) - Gödeke, J; Güth, C; Lampe, C; Reinke, J; Lagler, F; Lukacs, Z; Beck, M; Schweinitz, D von
Abstract : Background: Hunter syndrome (Mucopolysaccharidosis type II; X-linked inheritance; prevalence rate in Europe approximately 1:77000 male newborns) is a rare, progressive, multisystemic disease, caused by deficiency of the lysosomal enzyme Iduronate-2-sulfatase. Due to the very heterogeneous phenotype Hunter syndrome is often not diagnosed before pre-school age. This is unfortunate, because patients would significantly benefit from the earliest possible start of treatment containing enzyme replacement therapy. Early screening methods are possible, but due to the rarity of this disease they are too expensive to be performed in all newborns. An at-risk patient population screening provides opportunity for timely identification of the patients. All children with Hunter syndrome have an umbilical hernia and about 60% develop an inguinal hernia in early childhood. This is significantly more than in the general population. Methods: Since February 2012 an at-risk population screening (male sex < 18 years old, presence of an umbilical hernia, surgery for inguinal hernia) is carried out in Germany and Austria. Test centers are over 90 surgical test centers which operate on children routinely. Patients are screened via Iduronate-2-sulfatase enzymatic assay from dried blood spots cards and an additional questionnaire. Results and conclusion: We will present the first results after 6 months study period. In case of positive screening results, a routine screening for the above mentioned at-risk population should be discussed. Simultaneously, an extended study within the European Union can then be planned and organized. Acknowledgements: This work is supported by a research-grant from Shire ® Deutschland GmbH.